Principles of international political economy - Hallerberg, Mark 1967-; Kucik, Jeffrey; Mukherjee, Bumba (Oxford University Press, 2021)
A First Look at International Political Economy -- Fundamentals of Trade Politics -- Determinants of Trade Politics -- International Trade Law and Institutions -- The Politics of Foreign Direct Investment and Multinational Corporations -- Political Economy of International Finance -- Financial and Currency Crises -- Politics of the Global Environment -- Who Gets Foreign Aid and Why? -- Aid and/or Trade? International Politics and Development -- The Rise of the BRICs and Their Impact on Global Economic Governance
Includes bibliographical references and index
Keywords: Wirtschaftspolitik; Handelspolitik; Internationale politische Ökonomie / (DE-627)742453413 / (DE-STW)29729-3; International economic relations; Globalization / Economic aspects